PERILAKU RUSA JAWA (Cervus timorensis) DI PENANGKARAN TAMAN SAFARI INDONESIA - Wirdateti; W.R. Farida; M.S.A. Zein (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1997)
The behavior study of Java deer (Cervus timorensis) has done for three month in captive breeding study of Java deer (Cervus timorensis) had done for three months in captive breeding at Safari Park Indonesia, Cisarua, Bogor. The object of this study was the daily activities such as: grazing, ruminating, lying and other activities. The method used in this work was Time Sampling. Observations were conducted in six times on daylight and four times in night. The result showed that the average percentage of daily activities of Java deer were 44% for grazing, 27% for ruminating, 18% lying, 6% standing and 5% walking subsequently.